ANALISIS FAKTOR RESIKO PRE EKLAMPSIA BERAT PADA IBU HAMIL DI BLUD RSU KOTA BANJAR - Supriyatun (Bina Generasi : Jurnal Kesehatan, 2023)
Maternal and child health services are a major priority in Indonesia's health development because there is still a significant problem with maternal mortality and morbidity. A measure of health is the Maternal Mortality Rate (MMR). 2015 saw an MMR of 305 per 100,000 live births in Indonesia. MMR reduction to 183 per 100,000 live births by 2024 and to less than 70 fatalities per 100,000 live births by 2030 is a global SDG target. Pregnancy-related hypertension is currently the leading cause of death in Indonesia. When proteinuria is absent and other organs are also affected by severe preeclampsia, blood pressure is >160/110 mmHg at >20 weeks of gestation. Preeclampsia's specific etiology is unknown as of right now. Preeclampsia in pregnant women can be caused by a number of variables, including low education levels, overworked mothers, primiparity or grande multiparity, and birth spacing that is either too near or too far apart. This study was conducted at BLUD RSU Banjar City with the aim of identifying the risk factors for severe pre-eclampsia in pregnant women. Correlational or association research, a retrospective study with a cross sectional design, is this kind of investigation. 614 pregnant women make up the study's population, which was chosen at random to create a sample size of 61. The findings revealed no relationship between educational factors (p-value: 0.394), employment (p-value: 0.664), parity (p-value: 1.000), and the time between pregnancies (p-value: 0.835; greater than 0.05) and the incidence of severe pre-eclampsia in pregnant women at BLUD RSU Banjar City. The frequency of severe pre-eclampsia in pregnant women at BLUD RSU Banjar City is not significantly correlated with education, occupation, parity, or pregnancy spacing.